Anti-constitutional activities and cover organisations of national-socialist movement in Klaipėda region in 1935-1937 - Mindaugas Valiukevičius (Lietuvos Istorijos Studijos)
Nazi movement in Klaipėda region, alike any social-political phenomenon in the 1st half of the XX century, had its beginning and its end. The 1st national socialist organization in the region had been established as early as in 1928. In 10 years, i.e. in 1938 "nazification" of Klaipėda region was finished. Military tribunal decision to imprison SVG and CSA organizations' leaders did not put an end to national-socialist movement.